Le consentement tragique : Bérénice au miroir de Marie Mancini - Jennifer Tamas (Institut du Monde Anglophone, 2021)
“You are the emperor, Sire, and yet you weep”. I argue that Racine based his tragedy on the forced separation between Marie Mancini and Louis XIV, who is the first addressee of the play. No deaths, but love leads to renouncement. Despite the glamorous anecdote, the comparison between Marie and Bérénice sheds light on the role of women in seventeenth-century theater. Both the historical figure of Marie and Racine’s character embody a rarely acknowledged power of resistance, and their struggle aims at promoting a symbolic and tragic recognition. The focus on silence in dialectical tension with utterance offers a better understanding of consent and love throughout the play. Instead of the traditional analysis of the “King’s two bodies” applied to Titus, this article envisions Bérénice as the foremost character in terms of rhetoric and dramaturgy. Racine renews the Aristotelian conception of anagnorisis by using free consent as the outcome of the play. Bérénice both fights and tempts Titus before she sublimely sacrifices her love. Using the royal affair as the subtext of his play, Racine examines key notions such as misalliance and marriage, but he also magnifies feminine virtue conceived as a heroic act of resistance.